Rebel Rising : a memoir - Wilson, Rebel (Simon & Schuster, Incorporated, 2024)
"For decades, Rebel Wilson had single-mindedly focused on her career, making a name for herself through her iconic roles in Pitch Perfect, Bridesmaids, and Isn't It Romantic. Now, she's ready to chronicle the emotional and physical lessons she learned, as well as her most embarrassing experiences. A malaria-induced hallucination? An all-style martial arts fighting tournament? Junior handling at dog shows? And this was all BEFORE she moved to Hollywood! Rebel Rising follows Rebel Wilson's incredible journey of "making it," constantly questioning, "Am I good enough? Will I ever find love? Will I ever change and become healthy?" Rebel writes for the first time about the most personal and important moments in her life--from fertility issues, weight gain and loss, sexuality, overcoming shyness, rejections, and, well... okay there's at least one story thrown in about Brad Pitt! It's all here. This memoir shows us how to love ourselves while making us laugh uncontrollably." --